Onset of action and seizure control in Lennox-Gaustaut syndrome: focus on rufinamide - Russell P Saneto; Gail D Anderson (Dove Medical Press, 2009)
Russell P Saneto1, Gail D Anderson21Division of Pediatric Neurology, Seattle Children’s Hospital/University of Washington, Seattle, Washington, USA; 2Department of Pharmacy, University of Washington, Seattle, Washington, USAAbstract: Lennox-Gaustaut syndrome is an electroclinical epilepsy syndrome characterized by the triad of electroencephalogram showing diffuse slow spike-and-wave discharges and paroxysmal fast activity, multiple intractable seizure types, and cognitive impairment. The intractability to seizure medications and cognitive impairment gives rise to eventual institutionalized patient care. Only a small subset of seizure medications has been shown to be helpful in seizure control. Most patients take up to 3 medications at high therapeutic dosing and are susceptible to medication-induced side effects. The lack of medication efficacy in seizure control has led one meta-analysis to conclude that there is no single medication that is highly efficacious in controlling seizures in this syndrome. On this background, a new and structurally novel seizure medication, rufinamide, has been found to be beneficial in the treatment of seizures in this syndrome. In a multicenter, double-blinded, randomized, placebo-controlled study, rufinamide was found to reduce seizures by over 30%. More importantly, it reduced the frequency of the seizure type that induces most of the morbidity of this syndrome, the drop seizure, by over 40%. There were few side effects, the medication was well tolerated, and in the open labeled extension study, tolerance was not found. In this review, we describe the main electroclinical features of Lennox-Gaustaut syndrome and summarize the few controlled studies that have contributed to its rational treatment. Currently, there is no single agent or combination of agents that effectively treat the multiple seizure types and co-morbidities in this syndrome. Our focus will be on the role of the new medication rufinamide in seizure reduction in patients with Lennox-Gaustaut syndrome.Keywords: Lennox-Gaustaut syndrome, catastrophic pediatric epilepsy, rufinamide